Sacral Nerves Reconstruction After Surgical Resection of a Large Sacral Chordoma Restores the Urinary and Sexual Function and the Anal Continence - Luigi Valentino Berra; Daniele Armocida; Mauro Palmieri; Valerio Di Norcia; Luca D’Angelo; Massimo Mongardini; Massimo Vigliotta; Edoardo Maccari; Antonio Santoro (Neurospine, 2022)
Objective Chordomas are slow-growing tumors, with a high tendency to local relapse. En bloc resection is related to the most favorable outcome in terms of survival but is frequently associated with permanent neurological deficits involving sphincters and sexual functions. In the present article, we describe an innovative technique of en bloc resection followed by reconstruction of the sacral nerves with nerve grafts. Methods The chordoma was excised through a posterior approach after dividing the proximal and distal sacral nerves using the established technique. After that, a microsurgical S2-S3-S4 nerve reconstruction was performed connecting the proximal and distal stumps with sural nerve grafts withdrawn from both lower limbs. Results Immediately after surgery, the patient experienced complete impairment of sexual function and sphincters with urinary and fecal incontinence. After 6 months, there was a progressive recovery of sexual function and sphincter control. One year after the operation, the patient achieved an adequate sexual life (erection and ejaculation) and complete control of the bladder and anal sphincter. Conclusion Reconstruction of nerves sacrificed during sacral tumor removal has been shown to be effective in restoring sphincter and sexual function and is a promising technique that may significantly improve patients' quality of life.